Development Optimization and In-vivo Evaluation of Swellable Gastroretentive Tablet by 32 Factorial Design - Shep, Santosh Gyandev (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The present invention preferably relates to formulation and characterization of a swellable gastroretentive tablet comprising pregabalin to enhance its bioavailability and retention time in the stomach. Materials and Methods: Tablets were prepared by wet granulation method using hydroxypropyl methylcellulose (HPMC) K4M and Psyllium husk as swelling agents and all other excipients were used of pharmaceutical grade. Results and Discussions: The tablet showed mucoadhesion time, force and strength 7.5-12 h, 24-28 g and 2.35-3.62 N, respectively. Swelling index and drug release were found to be 216% and 99.2%, respectively. In-vivo imaging study and pharmacokinetic study showed retention of tablet in gastrointestinal tract of rabbit for 24 h and release up to 24 h. The results for stability study were also same as they were at the initial stages of the evaluation. The method was also found optimum and valid when it was optimized using design expert software. The data obtained was best fit into Korsmeyer–Peppas model indicating non-Fickian or anomalous release and as compared to other models as R2 value was found to be 0.9983. Conclusion: It can be concluded that using polymers such as HPMC K4M and Psyllium husk the objective of this study are meet. The probability value indicates model terms are significant. The probability value, i.e., P value found was also <0.0500. The desirability value was found 0.984 which is equal to 1. From desirability, it can also be concluded that results actually obtained matches with the software prediction, and hence, the formulation is also validated.